2010
DOI: 10.1152/ajplung.00437.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doxycycline on proliferation, MMP production, and adhesion in LAM-related cells

Abstract: Matrix metalloproteinases (MMPs) have been implicated in lung cyst formation in lymphangioleiomyomatosis (LAM). As doxycycline inhibits MMP activity in vivo, some patients take doxycycline, as one report has suggested a possible benefit in LAM. However, there have been no randomized controlled clinical trials of doxycycline for LAM, and any mechanism of action is unclear. Here, we examine previously proposed mechanisms of actions. Cell proliferation and adhesion were examined using 3-(4,5-dimethylthiazol-2-yl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 37 publications
3
30
0
1
Order By: Relevance
“…Therefore, despite tremendous progress in LAM, the urgent need remains for improved therapeutic strategies. Our promising preclinical results with Faslodex add to a growing list of agents approved by the United States Food and Drug Administration for their potential efficacy in LAM, including simvastatin (37), chloroquine (38), and doxycycline (39). Faslodex may be of particular benefit in premenopausal women, in whom higher estradiol concentrations may be associated with higher rates of lung function decline.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, despite tremendous progress in LAM, the urgent need remains for improved therapeutic strategies. Our promising preclinical results with Faslodex add to a growing list of agents approved by the United States Food and Drug Administration for their potential efficacy in LAM, including simvastatin (37), chloroquine (38), and doxycycline (39). Faslodex may be of particular benefit in premenopausal women, in whom higher estradiol concentrations may be associated with higher rates of lung function decline.…”
Section: Discussionmentioning
confidence: 84%
“…(23,24) Chang et al demonstrated the in vitro effect of doxycycline on LAM cell adhesion, as well as on MMP-2 and MMP-9, revealing a reduction in cell proliferation, although very high doses of doxycycline were required and there was no significant blockade of MMP expression. (25) These findings, however, are questionable, because, to date, there have been no pathophysiological studies involving animal models of the LAM lung. Although the mechanism of action of doxycycline remains unclear, it is speculated that it inhibits MMPs by inducing TIMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that administration of doxycycline to LAM patients resulted in lower levels of MMP-2, MMP-9 in serum and urine, decreased symptoms and improved life quality [36,37]. However, in vitro studies showed that there was no significant reduction in the level and activity of MMPs in the ELT3 -/-cells, derived from an animal model of LAM, the Eker rat, after doxycycline cells treatment [38]. Thus, the efficacy of doxycycline to inhibit MMPs activity in LAM patients needs to be further investigated.…”
Section: Lam Cell Phenotypementioning
confidence: 99%
“…mRNA of gp100, and MART-1 (spindle-shaped cells) and estrogen receptors was detected in these cells by RT-PCR. Cells were cultured in the presence of epidermal growth factor [52] and used to study the role of chemokines in LAM and angiomyolipoma [29] as well as the effects of doxycycline on the proliferation, production of MMPs and adhesion of LAM-related cells [38]. Yu et al [53] described a line derived from human angiomyolipoma.…”
Section: Cell Lines As a Model Of Lammentioning
confidence: 99%